Analysis of Sharia Maqashid on PKWT in the Job Creation Law Article 18 No. 35 of 2021 - Putri, Rahmawati Aulia; Agung, Wahyu Dwi (Trunojoyo Madura University, 2025)
This study analyzes the Fixed-Time Work Agreement (PKWT) in the Job Creation Law Article 18 No. 35 of 2021 through the perspective of Maqashid Sharia, focusing on the principles of Hifdzul Mal (property protection) and Hifzun Nafs (life protection). Indonesia's labor regulations were significantly changed by the Job Creation Law, including the removal of restrictions on the field of work that can use the outsourcing system. This change provides flexibility for the business world, but also poses challenges in protecting workers' rights. From Hifdzul Mal's point of view, this policy can improve business efficiency and encourage investment. However, from Hifzun Nafs' perspective, job uncertainty due to PKWT's flexibility has the potential to reduce workers' welfare. This research uses a qualitative method with a sharia maqashid approach that examines laws and regulations related to PKWT and the outsourcing system in the Job Creation Law. The analysis was carried out by examining legal documents, Constitutional Court decisions, and Maqashid Syariah theory to assess the implications of regulations on the welfare of workers and the business world. This research emphasizes the importance of comprehensive follow-up regulations and effective supervision mechanisms so that labor reform in the Job Creation Law can run according to the principles of justice and welfare in Maqashid Sharia.